2015
DOI: 10.3386/w21669
|View full text |Cite
|
Sign up to set email alerts
|

Is It Harder for Older Workers to Find Jobs? New and Improved Evidence from a Field Experiment

Abstract: , and anonymous reviewers for very helpful comments. This study was approved by UC Irvine's Institutional Review Board (HS#2013-9942). The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w21669.ack NBER working papers are circulated for discussion and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 28 publications
6
122
4
1
Order By: Relevance
“…In addition, the results suggest that older women are more discriminated against than men (also found by Neumark et al (2015) for the US) and manual workers more than non-manual workers. These patterns accord with stereotypical beliefs that the physical strengths and job performance of women and manual workers decline earlier than for men and white-collar workers (Böhm et al 2013;Colin and Loretto 2004).…”
Section: Discussion and Implications For Organizations And Social Parmentioning
confidence: 70%
“…In addition, the results suggest that older women are more discriminated against than men (also found by Neumark et al (2015) for the US) and manual workers more than non-manual workers. These patterns accord with stereotypical beliefs that the physical strengths and job performance of women and manual workers decline earlier than for men and white-collar workers (Böhm et al 2013;Colin and Loretto 2004).…”
Section: Discussion and Implications For Organizations And Social Parmentioning
confidence: 70%
“…More concretely, we add interactions with indicators of high-educated candidates, male candidates, candidates who reveal engagement in a cancer organisation, candidates who reveal engagement at a korfball sports club, candidates with two engagements, and candidates with three engagements. For both call-back outcomes, we find a significant interaction only with respect to gender: the male volunteering premium in terms of getting any positive reaction (an 15 While the size of our sample is substantially lower than the size of the data gathered in some recent large-scale correspondence experiments in the United States such as Kroft et al (2013) and Neumark et al (2015), it is at least comparable to many other recent (and well-published) field experiments included in the review study of Baert (2017). In addition, a post hoc power analysis shows that based on the variation in our dataset, we were able to distinguish rather small effects from zero effects.…”
mentioning
confidence: 60%
“…18 18 In a correspondence study of women's job applications in two U.S. cities, Lahey (2008) found that younger women were 40 percent more likely to receive callbacks than older women. Neumark, Burn and Button (2015) find considerably more age discrimination in hiring against older women than older men in a large resume correspondence study.…”
Section: Results: the Age Twist In Firms' Gender Preferencesmentioning
confidence: 99%